On some polynomials derived from (p,q)-calculus - Aracı, Serkan; Duran, Uğur; Açıkgöz, Mehmet; Aracı, Serkan (My University, 2016)
We consider the new generating functions of the Bernoulli, the Euler and the Genocchi polynomials under post quantum calculus. From those generating functions, we analyse the behaviours of the polynomials mentioned in the paper. By making use of the fermionic p-adic integral over the p-adic number fields, we derive a relation between the new and old polynomials. It turns out that some well known formulae are obtained as special cases.
Keywords: (p,q)-Calculus; Bernoulli Polynomials; Euler Polynomials; Generating Function; Genocchi Polynomials; q-Calculus